Analysis of Profitability and Liquidity Ratios to Evaluate the Financial Performance of PT Sreeya Sewu Tbk for the Period 2019–2023 - Putri Melati Sitinjak; Amran Manurung; E. Manatap Berliana Lumban Gaol (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to assess the financial performance of PT Sreeya Sewu Indonesia Tbk from 2019 to 2023 using profitability and liquidity ratios. Financial performance is a critical indicator for evaluating a company's ability to generate profits and manage short-term obligations. The profitability ratios used include Net Profit Margin (NPM), Return on Equity (ROE), and Return on Assets (ROA), while the liquidity ratios include the Current Ratio, Quick Ratio, and Cash Ratio. The data analyzed were derived from the company’s financial statements, particularly the balance sheets and income statements over a five-year period. The results reveal a consistent decline in the company's financial performance. The NPM fell from a positive 1.94% in 2019 to negative values in 2021 and 2022, indicating decreasing net income despite increasing revenue. ROE and ROA also showed deteriorating trends, with ROE falling as low as -30.10% in 2022 and ROA dropping to -7.26%, suggesting inefficiency in using equity and assets to generate profits. Furthermore, liquidity ratios such as the Quick Ratio and Cash Ratio were significantly below industry standards, indicating a limited ability to meet short-term liabilities. The COVID-19 pandemic played a pivotal role in this performance downturn, causing supply chain disruptions, reduced market demand, and higher operational costs. Although minor recovery signs were observed in 2023, the overall financial condition remained below industry benchmarks. These findings highlight the need for PT Sreeya Sewu Indonesia Tbk to implement strategic financial restructuring and improve efficiency to ensure long-term financial sustainability.